2017
DOI: 10.1111/bph.14057
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2 receptor signalling controls inflammation in acute pancreatitis via a PP2A‐dependent Akt/NF‐κB signalling pathway

Abstract: D receptors control pancreatic inflammation in AP by inhibiting NF-κB activation via a PP2A-dependent Akt signalling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 60 publications
1
77
0
Order By: Relevance
“…Conversely, liver dopamine (DA) levels were reduced in the same experimental condition ( Figure 3). Besides its crucial role as neurotransmitter in the central nervous system, recent findings suggest anti-inflammatory and protective effects that are induced by DA administration in experimental models of acute pancreatitis and hepatitis [55,56]. Consistent with the observed antiradical activity, both of the extracts reduced the LPS-induced levels of 3-HK ( Figure 2).…”
Section: Resultssupporting
confidence: 80%
“…Conversely, liver dopamine (DA) levels were reduced in the same experimental condition ( Figure 3). Besides its crucial role as neurotransmitter in the central nervous system, recent findings suggest anti-inflammatory and protective effects that are induced by DA administration in experimental models of acute pancreatitis and hepatitis [55,56]. Consistent with the observed antiradical activity, both of the extracts reduced the LPS-induced levels of 3-HK ( Figure 2).…”
Section: Resultssupporting
confidence: 80%
“…Moreover, dopamine or dopamine agonist was reported to inhibit the upregulation of proinflammatory cytokines in these immune cells . Additionally, stimulation of dopamine D 2 receptors reduces the increased expression of inflammatory cytokines of pancreatic acinar cells by inhibiting NF‐κB signaling in mice acute pancreatitis model in vitro . In this context, losartan may improve visceral function by activating peripheral dopamine D 2 receptors to suppress the cytokine signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation on intracellular signaling pathways demonstrated that DSC suppressed inflammatory responses by enhancing SOCS3 expression and suppressing activation of NF-κB and STAT3. NF-κB activation in acinar cells is a key intracellular event in AP and modulates a variety of inflammatory genes ( 24 ). STAT3 is activated by IL-6 trans-signaling and involved in pancreatic damage in AP ( 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%